2011
DOI: 10.1080/10871209.2011.559529
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Deer Hunter Attitudes Toward Regulatory Change Using Self-Selected Respondents

Abstract: State wildlife agencies are charged with managing wildlife populations of harvestable species. Opinions regarding how species should be managed differ dramatically and decisions are often made without comprehensive data. There is interest among deer hunters in Minnesota to change harvest regulations that benefit mature bucks. Beginning in 2005, research focused on the biological and social implications of changing deer regulations. We used data collected via random surveys, public input meetings, and an Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This similarity of attitudinal responses suggests that self‐selection in web surveys does not automatically bias attitudinal results. Our results are consistent with a body of literature that suggests attitudinal questions may be less sensitive to bias, making web‐based surveys an efficient and valid method to obtain public input on regulatory alternatives (Best et al , Peterson and Messmer , Cornicelli and Grund , Gigliotti ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This similarity of attitudinal responses suggests that self‐selection in web surveys does not automatically bias attitudinal results. Our results are consistent with a body of literature that suggests attitudinal questions may be less sensitive to bias, making web‐based surveys an efficient and valid method to obtain public input on regulatory alternatives (Best et al , Peterson and Messmer , Cornicelli and Grund , Gigliotti ).…”
Section: Discussionsupporting
confidence: 90%
“…We evaluated differences in attitudinal variables for practical significance using a procedure we termed ‘polar reclassification,’ in which we omitted neutral responses, compressed directional responses, and interpreted results by simple majority (Cornicelli and Grund ). We combined responses of Strongly Oppose and Oppose into Oppose, and responses of Strongly Support and Support into Support.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the most effective way to reduce ungulate populations is to increase the harvest of adult females (e.g., Ueno et al , Milner et al , Boulanger et al ), yet some hunters do not pursue females for nonobjective reasons. Such established beliefs make implementing new harvesting regimes difficult (Finch and Baxter , Cornicelli and Grund ).…”
mentioning
confidence: 99%
“…Recent studies, however, have shown that online surveys, when utilizing a mixed-mode design, can be a good option for obtaining respectable response rates while keeping costs relatively low (Greenlaw & Brown-Welty, 2009). Also, online surveys have proven to be a successful tool for human dimensions of wildlife research (i.e., Cornicelli & Grund, 2011;Graefe et al, 2011;Lesser, Yang, & Newton, 2011;Sexton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%